Psychedelic Drugs and Epistemological Validity of Mystical Experiences - Ali Shirvani (حکمت اسرا)
The emergence of mystical (quasi-mystical) experiences following the consumption of psychedelic drugs (hallucinogens) is one of those important proofs for their claimants to demolish epistemological validity of mystical experiences (mystical unveilings). By resorting to such deduction they try to claim that mystical experiences may always be aroused from abnormal physiological states of their experiencers, so they conclude that these experiences are not valid and cannot be confirmed that they manifest the reality. This article aims at investigating different aspects of the argument so as to show that it is deeply flawed because firstly, this argument is based on the existence of cognation between the experiences achieved by psychedelic drug users and those achieved by mystics and this is the case which cannot be proved by alleged evidences; secondly, even in case that the cognation in question is proved, it will exist between the former and those mystical experiences of extrovertive kind; thirdly, considering the extrovertive mystical experiences as invalid due to considering them as congeneric with quasi-mystical experiences achieved by psychedelic drugs is not accepted; fourthly, there is no reason represented proving the invalidity of quasi-mystical experiences. It has also been discussed in this article the criticism on the principle of “causal indifference” by Stace and also the Muslim philosophers' consideration toward the possibility of occurrence of perceptual connections with esoteric issues.